2017
DOI: 10.15747/jcn.2017.9.2.62
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Stress Factor Calculated from the Changes in the Measured Resting Energy Expenditure with Indirect Calorimetry in Patients Undergoing Pancreaticoduodenectomy

Abstract: Purpose: To predict the energy expenditure using the stress factor representing the ratio of the metabolic variation between pre-operation and post-operation in a pancreaticoduodenectomy (PD). Methods: This was a prospective study conducted on 17 patients (11 males and 6 females) who underwent PD at Chonbuk National University Hospital between March 2010 and October 2011. The rest energy expenditure was measured by indirect calorimetry 1 day before and 3 days after surgery. The height, weight, and fat free mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…And they found that all parameters were lowest at POD 5 [17]. Kim [11] also observed significant differences in levels of prealbumin, CRP, and TLC between 1 day before and 3 and 7 days after PD surgery. Park et al [9] showed that serum transferrin, Alb and TP levels were the lowest at the day of leaving hospital after pancreatobiliary surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And they found that all parameters were lowest at POD 5 [17]. Kim [11] also observed significant differences in levels of prealbumin, CRP, and TLC between 1 day before and 3 and 7 days after PD surgery. Park et al [9] showed that serum transferrin, Alb and TP levels were the lowest at the day of leaving hospital after pancreatobiliary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These values are quite low comparing to values from other studies. Kim [11] reported that the average energy intake by POD 3 from PN and oral intake was 1,050 kcal/day after PD surgery. Hwang et al [23] studied the effect of early postoperative enteral nutrition on postoperative outcomes and reported that the mean of daily calorie and protein intake in the early oral feeding group (847.0 kcal and 42.4 g, respectively) were significantly higher than those in the traditional oral feeding group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation